Selective Electrical Surface Stimulation to Support Functional Recovery in the Early Phase After Unilateral Acute Facial Nerve or Vocal Fold Paralysis - Kurz, Annabella; Volk, Gerd Fabian; Arnold, Dirk; Schneider-Stickler, Berit; Mayr, Winfried; Guntinas-Lichius, Orlando (Frontiers in Neurology, 2022)
This article addresses the potential clinical value of surface electrical stimulation in the acute phase of denervation after the onset of facial nerve or recurrent laryngeal nerve paralysis. These two nerve lesions are the most frequent nerve lesions in the head and neck area. In this review, we will work out several similarities concerning the pathophysiology features and the clinical scenario between both nerve lesions, which allow to develop some general rules for surface electrical stimulation applicable for both nerve lesions. The focus is on electrical stimulation in the phase between denervation and reinnervation of the target muscles. The aim of electrostimulation in this phase of denervation is to bridge the time until reinnervation is complete and to maintain facial or laryngeal function. There is some preliminary data that early electrostimulation might also improve the functional outcome. Because there are still caveats against the use of electrostimulation, the neurophysiology of denervated facial and laryngeal muscles in comparison to innervated muscles is explained in detail. This is necessary to understand why the negative results published in several studies that used stimulation parameters are not suitable for denervated muscle fibres. Juxtaposed are studies using parameters adapted for the stimulation of denervated facial or laryngeal muscles. These studies used standardized outcome measure and show that an effective and tolerable electrostimulation of facial and laryngeal muscles without side effects in the early phase after onset of the lesions is feasible, does not hinder nerve regeneration and might even be able to improve the functional outcome. This has now to be proven in larger controlled trials. In our view, surface electrical stimulation has an unexploited potential to enrich the early therapy concepts for patients with unilateral facial or vocal fold paralysis.